Beyond the Reader, Towards the Player: Reconceptualizing the Reader-Response Theory through Video-Games - Rachid Benharrousse (J-Lalite: Journal of English Studies, 2022)
The reader-response theory valorized the reader; without the latter, the text did not exist and had no meaning. The reader is deemed as an interpreter of an already rigid text. This theoretical limitation is evidenced in the understanding of the player in video-games. The scholarship equates the player to the reader in their passivity. The players, through playing, are not the object of the process of signification. They constitute their narratives across video-game categories. Role-playing reinforces the player’s identification within the game world beyond mere interpretation. The player’s lived experience is no longer separated from role-playing. Lived experience is intertwined with the gaming experience, which establishes double-faceted contextualization; the player’s lived experience shapes their gaming choices and vice versa. Hence, the players are not confined to being passive interpreters of an already assigned narrative; instead, they constitute their narratives, live within the game, and experience their video-games.